PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN DI MAMAS GERMAN RESTAURANT - Euis Rahmawati (Majalah Ilmiah Widyacakra, 2019)
By providing the best quality of service and understanding customer needs and complaints, satisfaction will be felt by customers so that they can create good relationships between buyers and sellers that will impact on the creation of customer loyalty. This research aimed to analyze the influence of service quality and customer satisfaction on customer loyalty at Mamas German Restaurant. The sample of this research is 50 respondents of guests at Mamas German Restaurant. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method, by means of questionnaires with likert scale. The analytical technique used is multiple linier regression analysis. Results of statistical analysis known that the service quality and customer satisfaction influenced on customer loyalty at Mamas German Restaurant is 40%, based on hypothesis testing with the F and t test results, it can be concluded that the service quality variable (X1) and customer satisfaction (X2) simultaneously (together} and significantly influence on customer loyalty variable (Y) with value of F-test is 15, 671 and sig 0,000. The service quality variable (X1) partially and significantly positive influenced on customer loyalty (Y) with value of t-test is 4,425 and sig. 0,000 and customer satisfaction variable (X2) significantly positive influenced on customer loyalty variable (Y) with value of t-test is 3,174 and sig. 0,003 at Mamas German Restaurant.